Periapical Cemento-Osseous Dysplasia in Anterior Maxilla - Francisca Lívia Parente Viana; Bruno Carvalho de Vasconcelos; Filipe No-Brechaves; Karuza Maria Alves Pereira; Marcelo Bonifácio Da Silva Sampieri (Journal of Clinical and Diagnostic Research, 2019)
Periapical cemento-osseous dysplasia is a reactional fibro-osseous lesion that affects the supporting tissues of vital teeth. A 33-year-old female was referred for endodontic retreatment of the right maxillary central incisor with chief complaint of pain. On radiographic examination, endodontic treatment in tooth 11 and external root resorption in the apex of tooth 12 were observed. Moreover, a radiopaque lesion circled by a radiolucent halo involving the roots of teeth 11 and 12 was also present. The cone beam computed tomography showed resorption and perforation of the cortical bone. The result of the histopathological examination combined with the clinical findings made it possible to confirm the diagnosis of periapical cemento-osseous dysplasia. This case report emphasises on the value of association between imaging findings and histopathological examination in the diagnosis of such lesions.